THE ROLE OF EMPLOYEE INVOLVEMENT TOWARDS CORPORATE PERFORMANCE AT PT. TATA GRAHA STABAT ASRI STABAT - Hengky Kosasih,; Sri Aprianti Tarigan,; Elyzabeth Wijaya,; Susanto, Susanto (Journal of Innovation Research and Knowledge, 2022)
Employee involvement is a vital aspect of total quality management solutions, and also in the success of any business. The need to both grow and succeed in an increasingly competitive marketplace has seen the implementation of various quality initiatives in different companies and organizations. Problem-solving and process improvements are crucial to the company’s quality initiatives, and demonstrate proactive actions are being taken to prevent problems. By involving workers in the decision making process in areas that affect their jobs, employee involvement programs aspire to give workers more control over how they perform their jobs, which leads to greater motivation and job commitment by the employee. PT. Tata Graha Stabat Asri Stabat is one of property company. Nowadays, PT. Tata Graha Stabat Asri Stabat face the decreasing in sales. Although the company have a good and price valuable in product, but cannot increased sales. Therefore, the objective of this research is to know if employee involvement has effect towards corporate performance at PT. Tata Graha Stabat Asri Stabat.This research design is using conclusive research. Conclusive research is in two types: Casual and Descriptive. Casual is concerning cause and effect (casual) relationships and descriptive research uses different verity of data collection methods like secondary data analyzed quantitatively. From data analyzed, it found that there is high positive correlation for Employee Involvement and Corporate Performance. The result of determination Analysis is 0,725. It means that, Employee Involvement have a high relationship on Corporate Performance as much as 72.5% and the rest, 27.5% is influenced by other factors.